2020
DOI: 10.3390/en13143737
|View full text |Cite
|
Sign up to set email alerts
|

Method of Averaging the Effective Thermal Conductivity Based on Thermal Response Tests of Borehole Heat Exchangers

Abstract: This work concerns borehole heat exchangers and their testing using apparatus for thermal response tests. In the theoretical part of the article, an equation was derived from the known equation of heat flow, on which the interpretation of the thermal response test was based. The practical part presents the results of several measurements taken in the AGH Laboratory of Geoenergetics. They were aimed at examining the potential heat exchange capacity between the heat carrier and rock mass. Measurement results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Parameter identification method includes two methods, i.e., direct method and parameter estimation method (PEM). The theory of direct method is infinite line source (ILS) model which solves the heat transfer problem of an infinite line source in the ground, and the result of ILS model shows that ground thermal conductivity tends to be proportional to the slope of the linear equation about the mean fluid temperature (normally assumed as the average of inlet and outlet fluid temperatures) and logarithm of time [10]. Therefore, ground thermal conductivity can be calculated by linear fitting of TRT data, besides, the borehole resistance can also be calculated simultaneously [6].…”
Section: Introductionmentioning
confidence: 99%
“…Parameter identification method includes two methods, i.e., direct method and parameter estimation method (PEM). The theory of direct method is infinite line source (ILS) model which solves the heat transfer problem of an infinite line source in the ground, and the result of ILS model shows that ground thermal conductivity tends to be proportional to the slope of the linear equation about the mean fluid temperature (normally assumed as the average of inlet and outlet fluid temperatures) and logarithm of time [10]. Therefore, ground thermal conductivity can be calculated by linear fitting of TRT data, besides, the borehole resistance can also be calculated simultaneously [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that a BHE with oval cross-section pipes has the potential to decrease the installation costs and increase the thermal performance of the BHE. In a thermal response test (TRT) conducted by Sapinska-Sliwa et al [7] for three types of BHEs, for instance, single U-tube, double U-tube, and coaxial BHE, the last configuration was found to be the best one in achieving the effective thermal conductivity of the ground. In another study, carried out experimentally and numerically by Janiszewski et al [8], a single U-tube BHE was used to inject thermal energy into the surroundings.…”
Section: Introductionmentioning
confidence: 99%